Analisis Pengaruh Pengelolaan Bahan Baku terhadap Efisiensi Biaya Operasional Pada PT. PLN (Persero) - Alvy Mulyaning Tyas; Sayidah, Nur; Assagaf, Aminullah; Shanty Ratna Damayanti; Jajuk Suprijati; Sutarmin (INVENTORY: JURNAL AKUNTANSI, 2025)
This study addresses the financial challenges faced by PT. PLN (Persero), particularly the high operational costs associated with managing energy raw materials such as coal and gas. Dependence on third-party procurement exacerbates these issues, highlighting the need for comprehensive solutions. The research aims to analyze the impact of raw material management on operational cost efficiency. Using a quantitative approach and multiple linear regression analysis, the study reveals that the proportion of renewable energy (X1) significantly improves efficiency, with a coefficient of 53.99 and p=0.001p = 0.001p=0.001, indicating that a 1% increase in renewable energy proportion enhances operational cost efficiency by Rp 53.99/kWh. Raw material procurement costs (X2) positively affect efficiency, with a coefficient of 8.10 (p<0.001), emphasizing the importance of effective procurement strategies. Conversely, the inventory value of raw materials (X3) negatively impacts efficiency, with a coefficient of -21.05 (p=0.037), suggesting that excessive inventory levels reduce efficiency. Although transportation costs (X4) show a negative coefficient of -14.67, their effect is statistically insignificant (p=0.356). Overall, the findings highlight the crucial role of transitioning to renewable energy, diversifying raw materials, and optimizing stock management in improving operational efficiency. These insights provide strategic directions for PT. PLN (Persero) to enhance independence in raw material management and achieve significant operational cost efficiencies.